Alternans in human atrial monophasic action potenial. Issue 11 (November 1977) - Pop, T; Fleischmann, D
Abstract : This report describes the case of a patient with a supraventricular tachycardia with a ventricular rate of 109/min and no visible P waves in the electrocardiogram. The recording of the monophasic action potential of the right atrium disclosed an atrial tachycardia with a rate of 218/min. There was an alternans of the phase 2 of repolarisation in the action potential. This report emphasises the fact that the phenomenon of alternans occurs in man, as in the experimental animal, at a cellular level.